Imigrantki w społeczeństwach Zachodu. Emancypacja i integracja - Barbara Pasamonik (Kultura i Społeczeństwo, 2008)
Gender plays a central role in the decision to migrate and the composition of the migration ﬂows. Emigration is the process experienced differently by women and men. The experience of immigration profoundly impacts on the public and private lives of women – their participation in the labour force, their religiousness, their marital roles and satisfaction, and their autonomy and self-esteem. One of the possible effects of migration is the emancipation of women. There is a direct connection between emancipation and integration. In contrast to integrated western societies emancipated immigrant women, immigrants from traditional cultures are not interested in the integration. They risk not only the loss of cultural identity, but also their own identity.